The Ontario Veterinary College and the Establishment of the University of Guelph - Woodger, Kevin; Stone, Elizabeth (Ontario History)

(untitled) (The Ontario Historical Society, 2016)
This paper examines the creation of the University of Guelph in the early 1960s from the perspective of the Ontario Veterinary College, one of the University’s three founding colleges. We argue that although there were concerns that OVC would be overshadowed if it were to join a traditional university, the prospect of the creation of the University of Guelph was greeted largely with enthusiasm and the College benefitted from a close association with a traditional university. Nevertheless the faculty and alumni of OVC were genuinely concerned that joining a traditional university would hamper its ability to train veterinarians and divert much needed funding to other disciplines. In contrast, in its sister school the Ontario Agricultural College, any fears associated with joining a university came from politicians and administrators rather than from within Ontario’s agricultural community.